The Lithuanian State as an Ideological Project - Dementavičius, Justinas (Politologija, 2018)
[only abstract in English; full article and abstract in Lithuanian] The main goal of this article is to describe the establishment of the first Lithuanian Republic in 1918 as an ideological project. The focus here is on three ideological systems that are usually treated as closely linked to modern Lithuanian statehood – nationalism, Romanticism and conservatism. First, I deal with the question of nationalism (mostly treated as a form of ethnic nationalism) being the main grounding point for an independent Lithuanian state. I defend the thesis that the discourse of a national-state-building process and nationalism as a main ideological form is too narrow and one-dimensional. It can’t shed light onto the ideological polysemy and the quarrels that took place in 1918 and afterward. The argument is based on the interpretation of nationalism as a thin-centered ideology as it was described by Michael Freeden. The second thesis stresses that collective (national) self-understanding is undeniably important, but this interpretation does not predispose any state-building attempts. It requires a radical reinterpretation and transformation of known political reality, and this can only be achieved with political Romanticism as was described by Carl Schmitt. Finally, I introduce in the question of the place of conservative ideology in the state-building process. Modern Lithuanian statehood was reached through a radical reform of an old political system. That is why conservative thought, which usually stands for traditions and the established order, seems like an unnatural ideological ally for a new Lithuanian state. But if one would treat conservative thought as an ideology dealing with the issue of change and pointing to a natural community and history, it is then possible to find some specific traces of conservative imagination.